Effects of propofol or sevoflurane anesthesia induction on hemodynamics in patients undergoing fiberoptic intubation for cervical spine surgery: A randomized, controlled, clinical trial - Chiara Robba; Ega Qeva; Beatrice Borsellino; Simone Aloisio; Giulia Tosti; Federico Bilotta (Wolters Kluwer Medknow Publications, 2017)
Background and Aims: In patients undergoing surgery for cervical myelopathy, induction of general anesthesia can induce systemic arterial hypotension that may worsen spinal cord hypoperfusion and precipitate spinal injury. In this randomized, controlled, clinical trial study, we compared the hemodynamic changes related to anesthesia induction with intravenous (IV) propofol- and sevoflurane-based inhalational induction in patients undergoing fiberoptic intubation for cervical spine surgery. Material and Methods: A total of 72 patients were studied. Hemodynamic effects were assessed measuring mean arterial pressure (MAP), and the echocardiographic evaluation of the left ventricular function. A Student's t-test with Bonferroni correction or Chi-squared test was used, when appropriate, to assess differences in hemodynamic (extent of MAP drop and incidence of episodes of severe arterial hypotension) and other variables (occurrence and duration of episodes of apnea). Results: Patients assigned to total IV anesthetic approach had a lower MAP, and more significant changes in cardiac function compared to those who received the inhalational approach (68.1 ± 9.3 mmHg vs. 75.5 ± 10.3 mmHg; 25% vs. 5.5%). Conclusion: Anesthesia induction with both propofol or sevoflurane is safe and effective. However, total IV anesthesia induction is associated with more pronounced MAP drop which can worsen spinal cord hypoperfusion.